Pelatihan dan Pendampingan Pemanfaatan Tools Artificial Intelligence untuk Guru - Brave A. Sugiarso; Arie S.M. Lumenta; Pingkan A.K. Pratasis (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The training and mentoring activities for the use of Artificial Intelligence (AI) tools for teachers were chosen with the aim of enhancing or improving teachers’ understanding and ability to implement AI technology in the educational environment. Initial interviews revealed a lack of knowledge and skills among teachers in utilizing AI tools, which affects the quality and effectiveness of learning. The methods applied in this community service include counseling and training, preceded by surveys and interviews. Teachers were given intensive training that included an overview of AI and how to apply AI tools in the teaching and learning process. Additionally, there was an implementation phase that required teachers to design and implement simple AI-based learning applications as supporting media. The AI tools used included Gamma, IlovePDF, chatPDF, and ChatGPT. The results showed significant improvements in teachers’ understanding and skills in using AI tools. Teachers were able to create AI-based learning applications aimed at enhancing interaction between teachers and students. Furthermore, teachers could reduce administrative workload and optimize resources. Thus, the use of AI can have a positive effect on the quality of learning. The implementation of AI also facilitates teachers’ work in managing administration, such as handling attendance, assessments, and lesson planning.